Marketing Strategy Analysis and Development of Artha Sari Catering Service - Panengah, Andika Putra; Wandebori, Harimukti (Journal of Business and Management, 2012)
In Indonesia, especially in its capital city which is Jakarta, the business opportunities that emerged in culinary are taken by business people to build new catering businesses. Artha Sari Catering Service is a catering that provides catering and also floral services for all kinds of events in Jakarta with various kinds of menu packages. On 2010 and 2011, Artha Sari got most of its revenue from institutions/companies/firms, and since Artha Sari doesn’t have any effective marketing strategy yet, the owner wants to focus its marketing more to institutions/companies/firms to increase the company revenue. One of the main competitors of Artha Sari is Kiki Catering. Therefore, Artha Sari should focus more in serving Indonesian cuisines and improve those Indonesian cuisines’ taste and presentations, set fixed discounted prices for certain menus to their loyal customers, create a membership system the loyal customers and give them fixed discounted price, build more partnership with institutions, companies, and firms, do a follow up for order confirmation, always have staffs to stand by in the office to take the order, improve the appearance of the waiters, improve the overall quality of its table decorations and make them have more characteristic, improve the overall quality website, participate in catering seminars and exhibitions, and build more partnership with buildings and institutions.Purpose: The purpose of this research is to figure out the current marketing strategy of Artha Sari and then to develop the marketing strategy for Artha Sari.Design/methodology/approach: The theory used are Business Strategy which focused on Competitive Strategy by Michael E. Porter, Business Model by Osterwalder, and also marketing mix to analyze the current marketing strategy of Artha Sari, and then to develop the marketing strategy for Artha Sari. The analyses are the current condition and the segmentation analysis of both Artha Sari and its competitor, which is Kiki Catering, the Business Model for Artha Sari, in-depth interview to respondents from different institutions/companies/firms, and comparison analysis between those two caterings.Findings: The end of the research shows that Artha Sari focus in serving certain menu packages. The events that Artha Sari has served and the partnerships that Artha Sari made are fewer compared to Kiki Catering. Artha Sari’s current marketing strategy is it serves both individuals/personal and institutions/companies/firms, provides good taste and presentation quality of various menu packages, good quality and appearance of waiters, and beautiful table and floral decorations, uses website, brochures, and word of mouth for its promotions channel, and creates good relationships to all customers, from personal to company staffs by making phone calls and visits them directly. The strengths of Artha Sari compared to Kiki Catering, are in their product and price factors, and its weaknesses which are in their promotion, process and people factors.Research limitations/implications: This research only cover two companies which are Artha Sari and Kiki Catering that located on East Jakarta, and menus only focus on packages menus.Practical implications: The outcome of this research is Business Strategy in form of new business model for Artha Sari that focused on Marketing Strategy which will generate a differentiation between Artha Sari and its competitor.Social implications: With the conducted marketing strategy, Artha Sari could attract more customers.Originality/value: This research has an outcome which is marketing strategy that useful for a catering service that is still conventional.Keywords: Catering, Business Strategy, Business Model, Marketing MixCategory: Business Strategy; Marketing.